PENGARUH PERSAINGAN PASAR JASA AUDIT TERHADAP KUALITAS AUDIT: PERANAN REGULASI ROTASI DAN REGULASI CORPORATE GOVERNANCE - Viska Anggraita; Fitriany Fitriany; Sandra Aulia; Arywati Arywati (Universitas Mercu Buana, 2016)
ABSTRACT Audit services market in Indonesia is currently dominated by Four Public Accounting Firm (KAP), which is an affiliate of the Big 4 International Accounting Firm. These Four Public Accounting Firm (KAP) holds 88% of the audit market in Indonesia. This figure shows that the audit market in Indonesia has a high level of concentration. Theoretically, the existence of a high concentration will reduce audit quality produced. This is why audit market competition received much attention from regulators to formulate public policy regulating auditors practice. The purpose of this study is to empirically investigate the effect of regulation of rotation to audit market concentration in Indonesia and the effect of audit market concentration on audit quality. In addition the study also aims to examine the effect of the implementation of corporate governance regulation on the relationship between audit market competition (market concentration) on audit quality. This study used secondary data from the Annual Report from companies listed in Indonesian Stock Exchange (IDX), KAP Activity Report, and Direktori Akuntan Publik.. Stock price and financial statements data derived from the Osiris database, IDX, ICMD and other data. Data analysis using the Least Square (LS) with panel data. In addition, trend analysis performed to analyze the market concentration in Indonesia. This study provide evidence that regulation of rotation decrease the audit market concentration in Indonesia and that market concentration (market competition) has positive (negative) effect on audit quality. Implementation of corporate governance regulation reduce the negative effect of audit service market competition on audit quality.Keywords: Audit Quality, audit market competition, regulation of rotation